Effect of ankle kinesio taping on vertical jump with run-up and countermovement jump in athletes with ankle functional instability - Ho, Yi-Hung; Chang, Chih-Han; Wu, Hong-Wen; Lin, Cheng-Feng (Journal of Physical Therapy Science, 2015)
[Purpose] Limited research has been performed in spite of biomechanical evaluation of jump landing with kinesio taping. Therefore, the main objective of this study was to evaluate the effect of kinesio taping applied to athletes. In this study, the authors wished to investigate the effect of kinesio taping during a vertical jump with run-up and countermovement jump on ankle functional instability. [Subjects and Methods] Ten male athletes with ankle functional instability (FI) were recruited in this study from a college volleyball team. Each participant was requested to perform two tasks, the countermovement jump and vertical jump with run-up. Infrared high-speed cameras and force plates were used to assess the effect of ankle taping. [Results] The results showed that the peak ground reaction force in the sagittal plane during a vertical jump with run-up slowed down after kinesio taping and that the peak ankle plantar flexion moment in both types of jump also decreased. [Conclusion] In conclusion, this study proved the effect of kinesio taping on ankle functional instability, which was evaluated by measuring the vertical ground reaction force and peak plantar flexion moment. Its finding may allow us to provide some recommendations for athletes and trainers.